EFFECT OF FARMERS AND HERDERS CONFLICT ON ENTREPRENURIAL PRACTICE IN SOUTHWESTERN NIGERIA - Mufutau Akanmu Popoola; Dr. Brimah A. N; Shittu Muili Olawale (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
This research examined the incidents of farmers and herdsmen conflicts with the interest in the experience in South Western Nigeria .Through inter application of structural functionalist and conflict theories, the study delved into the investigation of the causes and the impact of farmers and herders conflict on the entrepreneurship practice and security standard of the South western Nigeria with the aim of providing information on the intricacies of the conflicts in the Ondo and Oyo state, Nigeria.Standard questionnaire was used to obtained information from 195 respondents. Descriptive analysis was adopted in carrying out the findings. Therefore, a random sampling through distribution of questionnaire was done. In addition, the secondary data such as books, relevant research articles, newspapers and government publications in Nigeria was applied. Data analysis was done, the findings attested to the fact that farmers and herdsmen conflicts are not caused by a single reason but are stimulated by multi-causal factors which majorly includes limited resources in face of greater need, reprise attack and shortage of pasture lands even climate change among others and this have great effect on entrepreneurial practice and economic activities of the people. The study also discovered that farmers-herdsmen conflicts have disintegrative concequence on the Nigerian state inspite of the region. The study recommended that every arms of the society should seek the restoration of earlier symbiosis relationship between farmers and herdsmen in Nigeria and Peace studies should be integrate to our educational system and make it compulsory subject from primary school level up to university level.